2016
DOI: 10.15326/jcopdf.3.2.2015.0152
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between FEV1 and Patient-Reported Outcomes Changes: Results of a Meta-Analysis of Randomized Trials in Stable COPD

Abstract: This meta-analysis assessed the relationship between change from baseline (CFB) in spirometric measurements (trough forced expiratory volume in 1 second [FEV] and FEV area under the curve [AUC]) and patient-reported outcomes (St. George's Respiratory Questionnaire total score [SGRQ] CFB, Transition Dyspnea Index [TDI] and exacerbation rates) after 6-12 months' follow-up, using study treatment-group level data. A systematic literature search was performed for randomized controlled trials of ≥24 weeks duration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
0
9
1
Order By: Relevance
“…1). This review included a new analysis of data from a previous systematic literature review [6] and data found in a subsequent systematic literature search.
Fig. 1Data sources and selection criteria for the review.
…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). This review included a new analysis of data from a previous systematic literature review [6] and data found in a subsequent systematic literature search.
Fig. 1Data sources and selection criteria for the review.
…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria employed in this analysis were consistent with those employed in the previous analysis [ 6 ]. Only studies with the full texts published in English language were included.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations